Les enseignants en seconde carrière : un vivier de recrutement aux motivations spécifiques ? - Victoria David (Recherches en Éducation)
The increasing difficulties in attracting traditional student candidates for the teaching competitions are coupled with the increase in the flow of career changers in those competitions. This raises the question of the reasons why these individuals join the teaching profession. Analyses based on a quantitative methodology show that tenured teachers retraining in French general secondary education have a lower extrinsic motivation score than their first career counterparts. It lt also shows that the motivations to join teaching of these two populations are influenced by different factors. Second career teachers also appear to be a heterogeneous population in terms of motivations: analyses suggest that characteristics of the previous activity influence the way teaching is perceived as a potential career. These results underline the need to consider the broader scope of previous professional socialisation as an explanatory factor in the choice of a teaching career.